EFFICACY OF INTRA OPERATIVE USE OF TRIAMCINOLONE IN LUMBAR DISCECTOMY - Ishfaq, Asim; Shahzad, Muhammad (Pakistan Armed Forces Medical Journal, 2020)
Objective: To evaluate the effect of epidural application of triamcinolone during lumbar discectomy on postoperative pain relief. Study Design: Case control study. Place and Duration of Study: Department of Neurosurgery, Combined Military Hospital Lahore, from Oct 2019 to Feb 2020. Methodology: Thirty patients receiving intraoperative epidural triamcinolone application compared with 30 controls objective assessment by T-scores of the Timed Up and Go test, back and sciatic leg pain by Visual analog scale and for subjective functional impairment by oswestry Disability Index were calculated pre-op, postoperative day 2 and at 4 weeks. Results: The baseline demographics, disease specific features and preoperative impairment scores were similar among both groups. At day post-operative day 2, subjective impairment on oswestry disability index for the steroid group was (30.6 vs 36.2, p<0.01), with significant difference in terms of objective functional impairment score between steroid group (T-score 128.2 vs 129.3, p<0.01). At 4 weeks post operatively, the Objective functional impairment was also found to be significantly less in the steroid group (T-score 100.5 vs 110.3, p<0.01), with less disabled steroid group patients with oswestry disability index (17.0 vs 24, p<0.01). Complication rates in both groups were similar. The duration of hospital stay was shorter among the steroid group (5.0 vs 5.8 days, p=0.06). Conclusion: The application of triamcinolone in lumbar discectomy leads to benefit in both subjective and objective pain parameters in the early postoperative period.